Bioinformatics analysis of microarray profiling identifies the mechanism of focal adhesion kinase signalling pathway in proliferation and apoptosis of breast cancer cells modulated by green tea polyphenol epigallocatechin 3‐gallate. (5th September 2018) - Luo, Xiao; Guo, Lihua; Zhang, Lirong; Hu, Yu; Shang, Dongmei; Ji, Degang
Abstract: Objectives: This study aimed to investigate potential gene and signal pathway associated with tumour progression. Methods: Related microarray data set of breast cancer was obtained from Gene Expression Omnibus database, and differential‐expressed genes (DEGs) between two control samples and two treated samples were analysed using statistical software R. We collected 50 epigallocatechin‐3‐gallate(EGCG)‐related genes and 119 breast cancer‐related genes to create a knowledge base for following pathway analysis. Key findings: A total of 502 mRNAs were identified as DEGs based on microarray analysis. Upregulated DEGs mainly enriched in nuclear nucleosome, cell adhesion, DNA packaging complex, Wnt‐activated receptor activity, etc ., while the downregulated DEGs significantly enriched in ncRNA processing, mitotic nuclear division, DNA helicase activity, etc . DEGs mostly enriched in gap junction, cell cycle, oxidative phosphorylation, focal adhesion, etc . EGCG suppressed FAK signalling pathway. Furthermore, EGCG could inhibit breast cancer cell proliferation and promote apoptosis by modulating CCND1. Conclusions: Epigallocatechin 3‐gallate might exert influence on breast cancer progression through inhibiting focal adhesion kinase (FAK) signalling pathway.